CONCEPT AND LEGAL SIGNIFICANCE OF PAROLE - Gayratovna, Kamalova Dildora (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
General Background: The institution of parole plays a crucial role in the criminal justice system, allowing for early release from incarceration under specific conditions. Specific Background: This article provides a comprehensive analysis of the concept of parole, exploring its definitions, terms, and socio-legal implications, particularly within the context of Uzbek criminal law. Knowledge Gap: Despite the existing literature, there is a lack of thorough examination regarding the historical development, normative frameworks, and the comparative analysis of parole systems in various jurisdictions. Aims: The aim of this research is to elucidate the essence of parole, critically assess the legal framework governing its application, and analyze scholarly opinions from both Uzbek and international experts. Results: The findings reveal significant insights into the modifications and statutory changes concerning parole, supported by legal statistics and empirical data. Novelty: This study contributes to the discourse by integrating scientific methodological approaches to dissect the complexities of parole, offering a comparative perspective that enhances understanding of its global applications. Implications: The conclusions drawn from this research underscore the necessity for legal reforms and policy recommendations, aiming to improve the efficacy of parole as a rehabilitative measure within the criminal justice system. This article ultimately advocates for a balanced approach to parole, promoting both public safety and the reintegration of offenders into society.